2014
DOI: 10.1080/13811118.2013.809041
|View full text |Cite
|
Sign up to set email alerts
|

Mental Pain, Communication Difficulties, and Medically Serious Suicide Attempts: A Case-Control Study

Abstract: Medical severe suicide attempts (MSSA) are epidemiologically very similar to individuals who complete suicide. Thus the investigation of individuals who have made MSSAs may add to our understanding of the risk factors for completed suicide. The aim of this study was to assess the role of mental pain and communication difficulties in MSSA. A total of 336 subjects were divided into 4 groups: 78 meeting criteria for MSSA compared with116 subjects who made a medically non-serious suicide attempt (MNSSA), 47 psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 33 publications
5
59
1
Order By: Relevance
“…Further, Levi‐Belz et al. () reported that there were higher levels of mental pain in suicide attempters than in nonsuicidal psychiatric inpatients or healthy controls. Levinger, Holden, and Ben‐Dor () found that higher levels of suicidality were associated with stronger levels of mental pain and lower mental pain tolerance in young adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Levi‐Belz et al. () reported that there were higher levels of mental pain in suicide attempters than in nonsuicidal psychiatric inpatients or healthy controls. Levinger, Holden, and Ben‐Dor () found that higher levels of suicidality were associated with stronger levels of mental pain and lower mental pain tolerance in young adults.…”
Section: Introductionmentioning
confidence: 99%
“…To underline the importance of mental pain in suicide, Huanhuan et al (2014) used stepwise regression analyses to demonstrate that only pain avoidance (i.e., seeking escape from the psychological pain) is significantly associated with suicide ideation and suicidal acts. Further, Levi-Belz et al (2014) reported that there were higher levels of mental pain in suicide attempters than in nonsuicidal psychiatric inpatients or healthy controls. Levinger, Holden, and Ben-Dor (2016) found that higher levels of suicidality were associated with stronger levels of mental pain and lower mental pain tolerance in young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, difficulties in interpersonal relationships have been shown to be reflected in thwarted belongingness , an acknowledged risk factor for suicidality (Van Orden et al., ). In a project focusing on medically serious SAs, we found that low levels of self‐disclosure and lack of perceived social support comprise major risk factors for more lethal suicidal behavior (Levi‐Belz, Gvion, Horesh, & Apter, ; Levi‐Belz et al., ; Trakhtenbrot et al., ), above and beyond distress and personal factors.…”
mentioning
confidence: 99%
“…SD enables the forming of social relationships, allowing one to receive the help and support he may need [26]. Numerous studies have shown that authentic SD to at least one significant other person is a necessary prerequisite for healthy adjustment [27][28], as a buffer against stress and mental pain [29][30], and even as a facilitator for growth [31][32]. When individuals share intimate information, this may be an indication of their having formed social relationships, thus enabling them to receive help and support as needed [33].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to reveal one's true feelings and thoughts to another person is recognized as an important skill that can have a beneficial impact on both physical and mental health [9]. Regarding the other end of the SD continuum, several studies have found strong relationships between limited SD and various mental health characteristics, such as depression, anxiety disorders, and suicidal behavior [10][11][12].…”
Section: Introductionmentioning
confidence: 99%